Bupropion Ameliorates Acetic Acid–Induced Colitis in Rat: the Involvement of the TLR4/NF-kB Signaling Pathway - Rashidian, Amir; Dejban, Pegah; Karami Fard, Kiana; Abdollahi, Alireza; Chamanara, Mohsen; Dehpour, Ahmadreza; Hasanvand, Amin (Inflammation, 2020)
Inflammatory bowel disease composed of ulcerative colitis and Crohn’s disease is a disorder that may involve entire gastrointestinal tract. Its pathogenesis is mainly an immune-mediated inflammation. Recently, it has been indicated that bupropion possesses anti-inflammatory properties; hence, the objective of this experiment is the investigation of the anti-inflammatory influence of bupropion on colonic lesions that emerged following the intrarectal administration of acetic acid. Thirty-six male Wistar rats were allocated randomly into six groups, including control, acetic acid, dexamethasone (2 mg/kg), and bupropion (40, 80, and 160 mg/kg). Colitis was induced by intrarectal administration of acetic acid in all study groups except control group, and animals were treated by oral administration of dexamethasone and bupropion. While macroscopic and microscopic lesions were observed after colitis induction, administration of dexamethasone and bupropion 160 mg/kg led to the remarkable improvement in lesions. In addition, the expression of TLR4 and NF-ĸB was decreased after colitis induction; however, treatment with dexamethasone (2 mg/kg) and bupropion (160 mg/kg) resulted in a significant decrease in their expression. Regarding biochemical factors, following colitis induction, TNF-α level and MPO activity were increased; nevertheless, dexamethasone (2 mg/kg) and bupropion (160 mg/kg) decreased the TNF-α and MPO activity. In conclusion, bupropion exerts anti-inflammatory influence through suppressing the TLR4 and NF-ĸB expression in the rat model of acute colitis.